2022
DOI: 10.30762/jeels.v7i2.2060
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Undergraduate Students’ Perception of Kahoot Mediated E-Assessment

Abstract: This study is an endeavor to depict undergraduate students’ perception of a digital game-based learning (DGBL) platform called Kahoot! integrated into the undergraduate students’ learning. To this end, a sequential explanatory study was employed. Undergraduate students from a private university in Indonesia (N=21) agreed to participate in this study. A web-based five-point Likert scale questionnaire was developed to examine their perceptions of this platform. A focus-group interview was also conducted to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…This finding supports Fageeh (2015), who found that time limitations and internet connectivity problems, according to EFL students' perceptions, were the most significant obstacles to using online assessment. In addition, the findings of this study confirm what Sari et al (2020) and Mahbub (2020) stated, that poor internet connection was the most significant impediment to online assessments.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This finding supports Fageeh (2015), who found that time limitations and internet connectivity problems, according to EFL students' perceptions, were the most significant obstacles to using online assessment. In addition, the findings of this study confirm what Sari et al (2020) and Mahbub (2020) stated, that poor internet connection was the most significant impediment to online assessments.…”
Section: Discussionsupporting
confidence: 86%
“…As seen in the above-mentioned studies, integrating technology into EFL classes facilitates the evaluation process; however, a growing number of studies have highlighted some challenges experienced by EFL students and teachers alike (Chiang, 2020;Fageeh, 2015;Mahbub, 2020;Sari et al, 2020). For example, time constraints in Fageeh's (2015) study were the most significant challenge for learners in using online assessments, followed by internet connectivity problems.…”
Section: Challenges Of Online Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the research applied explanatory sequential mixed-methods because it was initially conducted with quantitative data in the form of questionnaire results, and then supported by qualitative data in the form of students' interview results and observation data from asynchronous and synchronous tools. The use of multi-method approaches considers being the appropriate method since it can support data analysis and data collection methods (Mahbub, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire was made electronically via Google form to obtain the necessary data. It was prepared and modified from some relevant research (Al-Said, 2015;Mahbub, 2020;Simbolon, 2021). The modifications included number of items, the name of the learning tools (Zoom and Edmodo), and the use of "bichronous" term which shifted online learning or blended learning.…”
Section: Methodsmentioning
confidence: 99%